How entrepreneurship education affects college students’ entrepreneurial intention: Samples from China - Jianpeng Fan; Junhao Hu; Jia Wang (Heliyon, 2024)
Colleges and universities play a pivotal role in nurturing students' entrepreneurial aspirations, as evidenced by a significant increase in entrepreneurial education. Improving its quality and igniting students' motivation are crucial. This study, grounded in established theoretical frameworks, introduces variables such as entrepreneurial intention, attitude, and self-efficacy, forming a moderated mediation model. An analysis of 347 questionnaires using Mplus 8.0 reveals the following insights: (1) Collegiate-level entrepreneurship education is positively correlated with students' entrepreneurial intentions; (2) Entrepreneurial attitude and self-efficacy mediate the relationship between entrepreneurship education and students' entrepreneurial intentions; (3) Entrepreneurial social support moderates the link between entrepreneurship education and students' entrepreneurial intentions. These findings contribute to the body of knowledge in entrepreneurship education and provide valuable guidance for enhancing its effectiveness and fostering students’ entrepreneurial aspirations.